2021
DOI: 10.1186/s12885-021-08244-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression-based immune infiltration analyses of renal cancer and their associations with survival outcome

Abstract: Background Renal cancer is a common malignant tumor with an increasing incidence rate. Methods In this study, based on the gene expression profiles, we analyzed the compositions of tumor-infiltrating immune cells (TIICs) in renal cancer and paracancerous samples using CIBERSORT. The proportions of 22 TIICs subsets in 122 paired renal carcinoma and paracancerous samples, and 224 Wilms tumor (WT) samples varied between intragroup and intergroup. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In the above results ( Figure 5B ), we identified several TIICs with statistically significant differences in proportion and reviewed the relevant literature using PubMed. Finally, we selected two types of TIICs, resting mast cells and T cells CD4 memory activated, to focus on the prognostic value of KIRC ( 23 , 24 ). The results indicated that lower levels of resting mast cells were significantly associated with worse OS (P = 0.001, Figure 6A ), histological grade (P < 0.001, Figure 6B ) and pathological stage (P < 0.001, Figure 6C ) deterioration, whereas T cells CD4 memory activated showed the opposite (P = 0.021, Figure 6D ; P < 0.01, Figure 6E ; P < 0.05, Figure 6F ).…”
Section: Resultsmentioning
confidence: 99%
“…In the above results ( Figure 5B ), we identified several TIICs with statistically significant differences in proportion and reviewed the relevant literature using PubMed. Finally, we selected two types of TIICs, resting mast cells and T cells CD4 memory activated, to focus on the prognostic value of KIRC ( 23 , 24 ). The results indicated that lower levels of resting mast cells were significantly associated with worse OS (P = 0.001, Figure 6A ), histological grade (P < 0.001, Figure 6B ) and pathological stage (P < 0.001, Figure 6C ) deterioration, whereas T cells CD4 memory activated showed the opposite (P = 0.021, Figure 6D ; P < 0.01, Figure 6E ; P < 0.05, Figure 6F ).…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + memory T cells are a subset of antigen-specific CD4 + T cells that persist after the primary T cells response’s expansion, constriction, and memory phases ( 36 38 ). It has emerged as a prognostic factor in various cancers, including kidney cancer ( 39 ), lung cancer ( 40 ), pancreatic cancer ( 41 ) and breast cancer ( 42 , 43 ). Heightened memory after secondary antigen stimulation, CD4 + T cells multiply and develop into specialized CD4 + T cells subsets that are specific to pathogens ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%